A study on an organization awareness towards green office movement among employees in selected public sector department at Yayasan Islam Terengganu / Nur Fatin Syahirah Muhammad - Muhammad, Nur Fatin Syahirah (Faculty of Business Management, 2016)
The purpose of this study was to identify the organization awareness towards green office movement among Malaysian employees. The type of this research was descriptive research. This study was conducted at the government sector namely Yayasan Islam Terengganu. The total respondents that involved in this study were 50 respondents. The instrument used to collect the data was by using questionnaire that consist of four sections which were demographic (section A), organization awareness (section B), green office practices (section C) and 3R concept (section D). All the data that had been collected were analyzed by using Statistical Package in the Social Sciences Software (SPSS Version 20). The result showed that the overall mean for organization awareness was 3.02 which the result was moderate and not all of them practiced the green office. Other than that, the mean for green office practices was 3.86 which was the respondents tend to agree with the statements. Besides that, the mean for 3R concept was 3.52 which it also was moderate. The recommendations for practices at Yayasan Islam Terengganu were to organize more talks about green office and visit other organization that implement green office. Meanwhile, the recommendations for future research were expand the study to private sector, increase the number of respondents and conduct correlational research.